Beyond the public space tableau: Insurgent heritage and the right to the city in Bogotá (Alternautas, 2023)
This paper explores how the right to the city is understood and practiced in relation to public space by contrasting two models of urban planning in Bogotá, Colombia. It contrasts a best practice right to the city/public space model with an alternative vision for urban ordering based on participatory forms of living heritage. I argue that this represents a kind of insurgent heritage that offers a potentially rich and powerful concept for extending the right to the city to further push for including alternative worldviews and practices in planning and policymaking. To develop this argument, I discuss theories related to public space, the right to the city, and critical heritage. I then use these to discuss an ethnographic study of heritage planning in the Traditional Center of Bogotá.